2012
DOI: 10.1371/journal.pone.0031794
|View full text |Cite
|
Sign up to set email alerts
|

New Model of Macrophage Acquisition of the Lymphatic Endothelial Phenotype

Abstract: BackgroundMacrophage-derived lymphatic endothelial cell progenitors (M-LECPs) contribute to new lymphatic vessel formation, but the mechanisms regulating their differentiation, recruitment, and function are poorly understood. Detailed characterization of M-LECPs is limited by low frequency in vivo and lack of model systems allowing in-depth molecular analyses in vitro. Our goal was to establish a cell culture model to characterize inflammation-induced macrophage-to-LECP differentiation under controlled conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
109
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(120 citation statements)
references
References 65 publications
(128 reference statements)
11
109
0
Order By: Relevance
“…Whether COX-2 inhibition is also acting directly on the lymphatic vasculature is unanswered by our current studies and merits further investigation. Furthermore, macrophages are an additional cell type thought to play crucial roles in both normal and tumor-associated lymphangiogenesis (30,(42)(43)(44). Since macrophages are increased in the postpartum involuting gland (4,45), we also recognize the importance of determining whether macrophages are driving lymphangiogenesis in the postpartum mammary gland.…”
Section: Methodsmentioning
confidence: 99%
“…Whether COX-2 inhibition is also acting directly on the lymphatic vasculature is unanswered by our current studies and merits further investigation. Furthermore, macrophages are an additional cell type thought to play crucial roles in both normal and tumor-associated lymphangiogenesis (30,(42)(43)(44). Since macrophages are increased in the postpartum involuting gland (4,45), we also recognize the importance of determining whether macrophages are driving lymphangiogenesis in the postpartum mammary gland.…”
Section: Methodsmentioning
confidence: 99%
“…Although this remains the mainstream theory, some recent evidence suggests that circulating progenitor cells might be incorporated directly into the growing lymphatic vessels and transdifferentiate into LECs (lymphovasculogenesis; Figure 1 and refs. [15][16][17][18][19][20]. Macrophage transdifferentiation was reported in an experimental orchitis model (15), LPS-induced peritonitis model (19), corneal injury model (16), and in a human transplanted kidney (17).…”
Section: Ialmentioning
confidence: 99%
“…[15][16][17][18][19][20]. Macrophage transdifferentiation was reported in an experimental orchitis model (15), LPS-induced peritonitis model (19), corneal injury model (16), and in a human transplanted kidney (17). Interestingly, under normal conditions the lymphatic endothelial progenitor cells appear only in minute quantities, but inflammatory stimuli lead to remarkable increases (18).…”
Section: Ialmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, associations between CD68+ macrophage populations and metastatic lymph node cancers have also been observed [13]. Experiments to establish the localisation of transplanted LECPs have shown that they are rapidly integrated into lymphatic vessels [11] but that there is a low incorporation frequency of them into new vessels of between 2% -5% [14], although one peritonitis model study reported a 50% incorporation of LECPs [15]. However, some of these studies have also shown that LECPs may be play a vital role in both the initiation of vessel formation and the maintenance of these vessels as they are present for a minimum of six months in the tissue under investigation [16].…”
Section: Discussionmentioning
confidence: 99%